Spatial patterns of discovery points and invasion hotspots of non‐native forest pests. Issue 12 (14th August 2019) - Ward, Samuel F.; Fei, Songlin; Liebhold, Andrew M.
Abstract: Aim: Establishments of non‐native forest pests (insects and pathogens) continue to increase worldwide with growing numbers of introductions and changes in invasion pathways. Quantifying spatio‐temporal patterns in establishment locations and subsequent invasion dynamics can provide insight into the underlying mechanisms driving invasions and assist biosecurity agencies with prioritizing areas for proactive surveillance and management. Location: United States of America. Time period: 1794–2018. Major taxa studied: Insecta, plant pathogens. Methods: Using locations of first discovery and county‐level occurrence data for 101 non‐native pests across the contiguous USA, we (a) quantified spatial patterns in discovery points and county‐level species richness with spatial point process models and spatial hotspot analyses, respectively, and (b) identified potential proxies for propagule pressure (e.g., human population density) associated with these observed patterns. Results: Discovery points were highly aggregated in space and located in areas with high densities of ports and roads. Although concentrated in the north‐eastern USA, discovery points also occurred farther west and became less aggregated as time progressed. Invasion hotspots were more common in the north‐east. Geographic patterns of discovery points and hotspots varied substantially among pest origins (i.e., global region of pests' native ranges) and pest feeding guilds. Significant variation in invasion richness was attributed to the patterns of first discovery locations. Data and shapefiles comprising analyses are provided. Main conclusions: Use of spatial point pattern analyses provided a quantitative characterization of the central role of human activities in establishment of non‐native pests. Moreover, the decreased aggregation of discovery points through time suggests that invasion pathways to certain areas in the USA have either been created or intensified by human activities. Overall, our results suggest that spatio‐temporal variability in the intensity of invasion pathways has resulted in marked geographic patterns of establishment and contributed to current macroscale patterns of pest invasion in the USA.